Chemical composition and productive performance of gestating sows, fed with taro tubers silage (Colocasia esculenta L. Schott) and panela cane (POJ93) - Caisedo, W.; Caisedo, L. (Cuban Journal of Agricultural Science, 2021)
In order to evaluate the chemical characteristics of taro tuber silage (Colocasia esculenta L. Schott) with panela cane (POJ93) and its effect on productive indicators of gestating commercial sows, a total of 30 F1 Landrace x Duroc sows with an average weight of 218.87 ± 2.85 kg were used. They were divided into two treatments (0 and 50% inclusion of silage in the diet), in equal parts, according to a completely randomized design. In the silage samples, the pH, dry matter, crude protein, crude fiber, ash, ether extract, nitrogenfree extracts and gross energy were determined. In the productive performance, the final weight of the sows, piglets born at birth, piglets born alive at birth, litter weight, piglet weight at born, food intake and the feeding cost per sow were evaluated. Data were processed by ANOVA and contrast of means with Fisher's test (P <0.05). The pH was stabilized between days four (4.15) and thirty (4.15). The silage showed good content of dry matter (70.99 %), crude protein (7.01 %), ash (13.16 %), nitrogen-free extract (72.42 %), gross energy (895.21 kJ/kg DM) and low content of ether extract (1.31 %) and crude fiber (6.13 %). There were no significant differences (P ˃ 0.05) between treatments for the final weight of the sows, piglets born at birth, total live born piglets, litter weight, piglet weight at born and food intake. The sows that were fed silage showed the lowest (P <0.05) feeding cost per sow. Under the Ecuadorian Amazon conditions, the inclusion of 50 % taro tubers silage (Colocasia esculenta L. Schott) with panela cane (POJ93) in the diet for gestating commercial sows did not affect the productive performance and reduced the cost production on the stage, so it constitutes an alternative food source with optimal nutritional characteristics for this category. Key words: alternative food, Ecuadorian Amazon, gestating commercial sows, taro and cane by-products.